2009
DOI: 10.3945/ajcn.2009.27680
|View full text |Cite
|
Sign up to set email alerts
|

Fish-oil supplementation induces antiinflammatory gene expression profiles in human blood mononuclear cells

Abstract: These results are the first to show that intake of EPA+DHA for 26 wk can alter the gene expression profiles of PBMCs to a more antiinflammatory and antiatherogenic status. This trial was registered at clinicaltrials.gov as NCT00124852.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
240
2
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(272 citation statements)
references
References 41 publications
(38 reference statements)
21
240
2
6
Order By: Relevance
“…Interestingly, when we incubated PBMC ex vivo with the fatty acids ALA or EPA, the same pattern with respect to the inflammatory response was observed, with EPA having the most prominent inflammatory potential compared with ALA. Anti-inflammatory effects on circulating markers have been observed in studies among healthy individuals after intake of fish oil supplements even though many studies also show no effect (27,28) . However, little is known about the postprandial or long-term effect of intake of fish oil on the expression of inflammatory genes in PBMC (22,29) . It has previously been shown that the n-3 fatty acid ALA has antiinflammatory activity (28) and inhibits expression and secretion of IL-6 from cultured human monocytes (30) .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when we incubated PBMC ex vivo with the fatty acids ALA or EPA, the same pattern with respect to the inflammatory response was observed, with EPA having the most prominent inflammatory potential compared with ALA. Anti-inflammatory effects on circulating markers have been observed in studies among healthy individuals after intake of fish oil supplements even though many studies also show no effect (27,28) . However, little is known about the postprandial or long-term effect of intake of fish oil on the expression of inflammatory genes in PBMC (22,29) . It has previously been shown that the n-3 fatty acid ALA has antiinflammatory activity (28) and inhibits expression and secretion of IL-6 from cultured human monocytes (30) .…”
Section: Discussionmentioning
confidence: 99%
“…The use of these cells in nutrition-related studies is increasing due to the number of different studies performed in both animals and humans that have demonstrated the relationship of PBMCs-captured metabolic changes with the fasting and feeding cycles (Bouwens et al 2007;Caimari et al 2010a, b;Oliver et al 2013) and with the intake of specific nutrients or bioactive food compounds such as fatty acids, proteins, carbohydrates and polyphenols (van Erk et al 2006;Crujeiras et al 2008;Bouwens et al 2009;Konstantinidou et al 2009;Khymenets et al 2009;Bouwens et al 2010;Camargo et al 2010;Rudkowska et al 2011;Van Dijk et al 2012a, b;Tomé-Carneiro et al 2013;van der Velpen et al 2013; Electronic supplementary material The online version of this article (doi:10.1007/s12263-014-0438-y) contains supplementary material, which is available to authorized users. Afman et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The suitability of leukocytes for gene profiling is related to their active metabolism [22] and accessibility by simple venipuncture [21,23], which may allow a repeated time-series analysis of changes in gene expression in response to changing environmental or disease factors. Previous studies have demonstrated the potential of using gene expression levels of peripheral blood leukocytes as a novel biomarker of nutritional interventions [24], to predict weight loss regain in obese subjects [25,26], and to predict the inflammatory response to functional foods [27].…”
Section: Discussionmentioning
confidence: 99%